2021
DOI: 10.2196/26931
|View full text |Cite
|
Sign up to set email alerts
|

Digital Interventions on Healthy Lifestyle Management: Systematic Review

Abstract: Background Digital interventions have tremendous potential to improve well-being and health care conveyance by improving adequacy, proficiency, availability, and personalization. They have gained acknowledgment in interventions for the management of a healthy lifestyle. Therefore, we are reviewing existing conceptual frameworks, digital intervention approaches, and associated methods to identify the impact of digital intervention on adopting a healthier lifestyle. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 139 publications
(190 reference statements)
1
75
0
Order By: Relevance
“…This section gives a detailed analysis and explanation of a tethered PHR mobile application, (e.g., the health eCoach system [ 49 , 50 , 51 , 52 , 53 , 54 ]) design and its implementation. We have used HL7 FHIR, HAPI library, SNOMED-CT, and PostgreSQL to ensure a bi-directional communication between the eCoach mobile app and PostgreSQL and used API security methods [ 55 , 56 ] to protect HAPI REST APIs.…”
Section: Methodsmentioning
confidence: 99%
“…This section gives a detailed analysis and explanation of a tethered PHR mobile application, (e.g., the health eCoach system [ 49 , 50 , 51 , 52 , 53 , 54 ]) design and its implementation. We have used HL7 FHIR, HAPI library, SNOMED-CT, and PostgreSQL to ensure a bi-directional communication between the eCoach mobile app and PostgreSQL and used API security methods [ 55 , 56 ] to protect HAPI REST APIs.…”
Section: Methodsmentioning
confidence: 99%
“…Overview Chronic illness associated with modi able lifestyle factors will be accountable for the highest death rates worldwide [1][2][3][4][5][6][7]. Lack of physical activities, improper dietary habits, excess consumption of tobacco and alcohol are severe risk factors for chronic diseases, such as obesity, overweight, hypertension, diabetes type II, cardiovascular diseases (CVDs), osteoporosis, and several types of cancer [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Overview Chronic illness associated with modi able lifestyle factors will be accountable for the highest death rates worldwide [1][2][3][4][5][6][7]. Lack of physical activities, improper dietary habits, excess consumption of tobacco and alcohol are severe risk factors for chronic diseases, such as obesity, overweight, hypertension, diabetes type II, cardiovascular diseases (CVDs), osteoporosis, and several types of cancer [1][2][3][4][5][6][7]. The World Health Organization (WHO) recommends for adults aged 18-64 years at least 150-300 minutes of moderateintensity aerobic exercise or at least 75-150 minutes of high-intensity aerobic exercise or an equivalent combination of medium and high-intensity exercise throughout the week [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence shows that web-delivered interventions can improve diet [ 1 - 3 ], physical activity [ 1 - 16 ], and weight management [ 10 , 17 , 18 ] in survivors of cancer [ 19 - 21 ]. Previous studies have reported positive associations between the lifestyle intervention website use by survivors of cancer and improvements in diet (ie, vegetable consumption) [ 2 ], physical activity (ie, aerobic and resistance-based) [ 13 , 22 ], and behavioral outcomes [ 3 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%